Developing a learning management system selection framework for a Filipino non-traditional school a case study - Laurente, Priscilla Saguiguit; Que, Elenita N.; Maligalig, Jon Paul F.; Manzano, Virgilio U. (Quezon City College of Education, University of the Philippines Diliman, 2021)
The change in teaching era has come to comprehend and adapt in the academic curriculum and instruction on technology integration and the concept of e-Learning was considered further attention. Recent research examined that obstacles hindering technology integration includes traditional teaching beliefs, approaches, and practices. Another reported impediment was a lack of teacher professional development such as experiences, skills, and technological mindset. The Learning Management System (LMS) operates asynchronous and synchronous course delivery options aligned with principles of effective multimedia learning. The study identified the influences of online education towards the behavior and skills on LMS usage, the selection of preferred LMS with standards features, and developed a decision framework instituting in a Filipino non-traditional school. The study used mixed method approach of explanatory design through survey questionnaire, interviews, and hands-on computer software application testing. Based on the findings, the study showed a positive attitude of the respondents about LMS usage.
Thesis
Keywords: Instructional systems -- Design; Education -- Effects of technological innovations on -- Philippines -- Manila Metropolitan Area; Teaching -- Aids and devices -- Philippines -- Manila Metropolitan Area; Educational technology -- Philippines -- Manila Metropolitan Area; Distance education -- Philippines -- Manila Metropolitan Area; Computer-assisted instruction -- Philippines -- Manila Metropolitan Area; Internet in education -- Philippines -- Manila Metropolitan Area